Hypoxia-Inducible Factor 1 Is an Inductor of Transcription Factor Activating Protein 2 Epsilon Expression during Chondrogenic Differentiation - Niebler, Stephan; Angele, Peter; Kujat, Richard; Boßerhoff, Anja Katrin (BioMed Research International, 2015)
The transcription factor AP-2? (activating enhancer-binding protein epsilon) is expressed in cartilage of humans and mice. However, knowledge about regulatory mechanisms influencing AP-2? expression is limited. Using quantitative real time PCR, we detected a significant increase in AP-2? mRNA expression comparing initial and late stages of chondrogenic differentiation processes in vitro and in vivo. Interestingly, in these samples the expression pattern of the prominent hypoxia marker gene angiopoietin-like 4 (Angptl4) strongly correlated with that of AP-2? suggesting that hypoxia might represent an external regulator of AP-2? expression in mammals. In order to show this, experiments directly targeting the activity of hypoxia-inducible factor-1 (HIF1), the complex mediating responses to oxygen deprivation, were performed. While the HIF1-activating compounds 2,2'-dipyridyl and desferrioxamine resulted in significantly enhanced mRNA concentration of AP-2?, siRNA against HIF1? led to a significantly reduced expression rate of AP-2?. Additionally, we detected a significant upregulation of the AP-2? mRNA level after oxygen deprivation. In sum, these different experimental approaches revealed a novel role for the HIF1 complex in the regulation of the AP-2? gene in cartilaginous cells and underlined the important role of hypoxia as an important external regulatory stimulus during chondrogenic differentiation modulating the expression of downstream transcription factors.
EVALuna2:4720